KONSEP PENDIDIKAN AKHLAK MENURUT IMAM AL-MAWARDI DALAM KITAB AD-DUNYA WA AD-DIN - Siti Marisa, Fadilla Gusti Ayu, Nurdiani, (Fakultas Agama Islam, 2022)
Imam Al-Mawardi is an Islamic thinker who lived during the heyday of Islamic civilization. This is evidenced by his work, namely the book Ad-Dunya Wa Ad-din. The book describes his concepts and views on moral education. This study aims to find out how the concept of moral education according to Imam Al-Mawardi in the Book Ad-Dunya wa ad-Din, what are included in the moral aspects according to Imam Al-Mawardi in the Book Ad-Dunya wa ad-Din, and how is the relevance of Imam Al-Mawardi's concept of moral education to the current concept of education. In conducting this research, researchers used deductive qualitative research methods. While the method used to collect data is through the essays of Imam Al-Mawardi which are documented in his masterpiece, namely the book Ad-Dunya wa Ad-Din. To analyze the data, the researcher uses a qualitative deductive analysis technique, namely to describe the existing data to describe the reality described in his book according to the actual phenomenon. The results of the study show that the concept of moral education according to Imam Al-Mawardi in the Book of Ad-Dunya wa ad-Din is divided into two parts, namely: 1) Moral education through a process of imitation and habituation, namely moral education taken through a predetermined pilot or imitation process the method is by ethicists (akhlak) and is based on the opinions of scientists, 2) Moral education is through a process of training and awareness, that is, something that is created is formed by a situation that cannot be refuted by reason and experts cannot debate the pros and cons of these rules, because the reason is logical and the truth is clear because it is supported by evidence.